A homozygous truncating variant in CCDC186 in an individual with epileptic encephalopathy. Issue 1 (1st December 2020) - Brugger, Melanie; Becker‐Dettling, Fiona; Brunet, Theresa; Strom, Tim; Meitinger, Thomas; Lurz, Eberhard; Borggraefe, Ingo; Wagner, Matias
Abstract: Coiled‐Coil Domain Containing Protein 186 (CCDC186) is hypothesized to play an important role in the biogenesis of dense‐core vesicles in neurons and endocrine cells. Biallelic loss‐of‐function variants in the encoding gene CCDC186 have been suggested as a candidate gene for a neurodevelopmental phenotype, but only one patient has been described so far. We report a second patient with a CCDC186 ‐associated phenotype presenting with developmental delay, epileptic encephalopathy, and failure to thrive. Exome sequencing identified a homozygous loss‐of‐function variant in CCDC186 (NM_018017.2) c.767C> G; p.(Ser256Ter) thus providing further evidence to support CCDC186 as a new disease gene for an autosomal recessive neurodevelopmental disorder.